2020
DOI: 10.1111/pere.12329
|View full text |Cite
|
Sign up to set email alerts
|

Childhood parental warmth and heart rate variability in midlife: Implications for health

Abstract: The current study investigated high-frequency heart rate variability (HF-HRV) as a potential mediator between childhood parental warmth and later health and mortality outcomes. Participants were 1,255 adults (56.9% female). Childhood parental warmth was reported retrospectively at mean age 46; resting HF-HRV was measured at mean age 57; cardiovascular health and self-evaluated health were assessed at mean ages 57 and 63, and mortality records extracted at mean age 63. Results revealed a positive association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…In the psychobiological literature, social support has been identified as a buffer against stress and a key promoter of resilience (Gunnar & Hostinar, 2015;Hostinar, 2015;Parenteau et al, 2020;Perry et al, 2021). Decades of correlational studies and laboratory experiments with children and adults alike have shown that social and emotional support can reduce the reactivity of the HPA axis and other stress-response systems, resulting in healthier biological profiles (Alen et al, 2020;Hostinar, 2015). Social support can not only reduce measures of allostatic load (McEwen & Gianaros, 2011), but can protect against the development of mental health problems.…”
Section: Social Cohesionmentioning
confidence: 99%
“…In the psychobiological literature, social support has been identified as a buffer against stress and a key promoter of resilience (Gunnar & Hostinar, 2015;Hostinar, 2015;Parenteau et al, 2020;Perry et al, 2021). Decades of correlational studies and laboratory experiments with children and adults alike have shown that social and emotional support can reduce the reactivity of the HPA axis and other stress-response systems, resulting in healthier biological profiles (Alen et al, 2020;Hostinar, 2015). Social support can not only reduce measures of allostatic load (McEwen & Gianaros, 2011), but can protect against the development of mental health problems.…”
Section: Social Cohesionmentioning
confidence: 99%
“…The 10 papers in the special issue highlighted the breadth of current mechanistic work on relationships and health. Although seven papers focused on romantic relationships and health, two examined parent–child relationships (Alen, Sloan, Seeman, & Hostinar, 2020; Woods, Roberson, & Priest, 2020), and one (Maki, 2020) considered the impact of romantic partners, friends, and family members on health outcomes. The samples included individuals at all stages of adulthood, ranging from emerging adulthood (Cortez, Lee, & Roberson, 2020) to older adults (Jaremka, Kane, Sunami, Lebed, & Austin, 2020).…”
Section: Variety and Common Themesmentioning
confidence: 99%
“…Moreover, some examined unique samples at high risk for poor health, such as individuals who have recently lost a spouse (LeRoy et al, 2020) or couples with one partner who has cancer (Ramos et al, 2020). The papers also investigated the effects of relationship functioning on several different types of health outcomes, including biomarkers (Jaremka et al, 2020; Maki, 2020), perceived health (Ramos et al, 2020; Roddy & Doss, 2020; Stanton, Spence, Kähkönen, & Dobson, 2020; Woods et al, 2020), health behavior (Crowley, Burke, Denes, Allred, & Carberry, 2020), symptoms and diagnoses (Cortez et al, 2020; LeRoy et al, 2020; Woods et al, 2020), and mortality (Alen et al, 2020). Most of the papers documented significant associations between relationship functioning, mechanistic variables, and health outcomes.…”
Section: Variety and Common Themesmentioning
confidence: 99%
See 2 more Smart Citations